Nanoparticle-Encapsulated Liushenwan Could Treat Nanodiethylnitrosamine-Induced Liver Cancer in Mice by Interfering With Multiple Critical Factors for the Tumor Microenvironment - Hong, Jing; Chen, Xi-Zhen; Peng, You-Gong; Zhang, Wei Kevin; Tang, He-Bin; Li, Yu-Sang (Frontiers in Pharmacology, 2020)
We previously isolated an ethanol fraction of LSW (Liushenwan pill, a traditional Chinese medicine) which has been shown to prevent and treat liver cancer induced by nanodiethylnitrosamine (nanoDEN) in mice. In the present study, we utilized a high-pressure microfluidics technique to generate LSW lipid nanoparticles (nano-LSW) to reduce its toxicity, and enhance its inhibitory effect on tumor growth, and further evaluate its therapeutic effect using a nanoDEN-induced mouse model of liver cancer. Our in vitro results indicated that nano-LSW-low could induce apoptosis in HepG2 cells, but exhibited low toxicity in L02 cells. Furthermore, the in vivo results indicated that nano-LSW-low exerted minimal or no damage to normal hepatocytes, kidney, and small intestine tissues. In addition, our results showed that at the 20th week, the inflammatory infiltration in the mice in the model group increased severely, and partial pimelosis and fibrosis occurred. In contrast, the liver tissues in the mice treated with nano-LSW exhibited only slight inflammatory infiltration, without pimelosis and fibrosis. At the 30th week, 4 out of 5 liver tissues in the model group showed hyperplastic nodules by hematoxylin and eosin (H&E) staining. However, the liver tissues in the nano-LSW treatment group did not showed hyperplastic nodules. Immunohistochemical staining showed that, in contrast to the model group, the levels of COX-2, PCNA, β-catenin and HMGB1 protein expressions were significantly lower in the nano-LSW-low group at the 20th and 30th week. Compared to model group, the COX-2, TNF-α, Smad-2 and TGF-β1 mRNA levels obviously decreased in the liver tissue after the nano-LSW-low treatment. Taken together, nano-LSW-low may serve as a potent therapeutic agent for preventing liver cancer by interfering with multiple critical factors for the tumor microenvironment during oncogenesis.